2014
DOI: 10.1007/s00417-014-2608-4
|View full text |Cite
|
Sign up to set email alerts
|

One-year refractive results, contrast sensitivity, high-order aberrations and complications after myopic small-incision lenticule extraction (ReLEx SMILE)

Abstract: In this first cohort, ReLEx SMILE produced satisfactory refractive outcomes with moderate induction of HOA and unaffected contrast sensitivity after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
88
4
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(113 citation statements)
references
References 10 publications
15
88
4
6
Order By: Relevance
“…With regard to contrast sensitivity, a study on SMILE by Sekundo et al 16 found no significant decrease in mesopic contrast postoperatively, whereas in another comparative study between SMILE and FS-LASIK, Gertnere et al 17 found better mesopic contrast sensitivity in the SMILE group than in the LASIK group. Montés-Micó et al found a statistically significant reduction (P < .01) in contrast sensitivity at high spatial frequencies (12 and 18 cycles/degree) under mesopic conditions following LASIK.…”
Section: Discussionmentioning
confidence: 96%
“…With regard to contrast sensitivity, a study on SMILE by Sekundo et al 16 found no significant decrease in mesopic contrast postoperatively, whereas in another comparative study between SMILE and FS-LASIK, Gertnere et al 17 found better mesopic contrast sensitivity in the SMILE group than in the LASIK group. Montés-Micó et al found a statistically significant reduction (P < .01) in contrast sensitivity at high spatial frequencies (12 and 18 cycles/degree) under mesopic conditions following LASIK.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the limited literature on the small-incision lenticule extraction and femtosecond lenticule extraction techniques, all relevant articles were included in the review. Figures 1 to 3 were developed from summation and percentage data in several articles on small-incision lenticule extraction 2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and LASIK [26][27][28][29][30][31][32] ; attempts were made to ensure uniformity in the preoperative refractive parameters and other potentially confounding variables. The significant disproportion of available published literature on each technique resulted in a significantly larger portion of LASIK patients (n Z 36 822) than small-incision lenticule extraction patients (n Z 1759).…”
Section: Methodsmentioning
confidence: 99%
“…Information was extracted from several studies. 2,11,12,14,[16][17][18][19][20][21]23 Sample sizes for each time period are as follows: 1 month, n Z 162; 3 months, n Z 958; 6 months, n Z 217; 1 year, n Z 73 (CDVA Z corrected distance visual acuity). a combination of keratectomy with subsequent excimer laser ablation was successfully performed, further refining the keratomileusis procedure.…”
Section: Historical Synopsismentioning
confidence: 99%
“…We perform Schirmer's test to establish the quantity of tear film. At the end of the initial examination, the patient is informed about the suggested surgical method, surgical procedure, possible complications and postsurgical regime 11,12,15 . Surgeries were performed by the standard procedure.…”
Section: Presurgical Examination Of Patientmentioning
confidence: 99%